TEACHING SPEAKING BY USING CLASS MEETING STRATEGY FOR JUNIOR HIGH SCHOOL STUDENTS - LENDRA, REVIA (Pendidikan Bahasa Inggris, 2014)
INTRODUCTIONSpeaking is a tool for communication. Every people can speak each other, make interaction, and share their thinking and ideas by using speaking. So that, every people should be able to speak well. In school program, speaking is the most important skill that should be master well by the students. It is because speaking can influence teaching and learning process. It means that through speaking, the teacher can make an interaction and communication with the students. By speaking, they also can do a discussion about the lesson during teaching and learning process.To make the students can speak well, the teacher should ask the students to do more practice in speaking both in the classroom and outside the classroom. The teacher can ask the students to speak with their friends. The teacher also can lead a class discussion to motivate the students to speak in the classroom. The most important things, in teaching speaking process, the teacher should be able to make the students fell enjoy to speak without fell nervous and afraid. If the teacher is able to make the students fell enjoy speaking so that the students will be able to speak well.In fact, based on the writer experience when doing teaching practice at junior high school, the writer found that there were many students who still have some problems in speaking although they have learnt speaking since in the elementary school, such as they are ashamed and nervous when speak in front of the classroom because they thought that their friends would laugh at them if they made a mistake so that they remain to keep silent when the teacher ask them to speak. They also could not find a suitable word to express themselves when they are speaking. It was supported by the writer interview to some English students about their difficulty in speaking. They said that they cannot speak English well because they do not know how to say some words in English. It can be said that they have lack of vocabulary so that they do not have motivation to speak.The studentsâ speaking ability also determine by the teacherâs strategy in teaching. In making the students master in speaking, the teacher also should have useful strategy in teaching speaking. However, based on the fact that the writer found when doing interview to some English teacher at Junior High School, the writer found that the teacher strategy in teaching speaking was still not able to make the students master in speaking. The teacher only asks the students to practice a dialogue with their friend in front of the classroom. The teacher did not teach the students how to express their ideas well.Actually, there are so many strategies that can be used by the teacher in teaching speaking to improve the students speaking skill. One of the strategies is by using class meeting strategy to improve studentsâ speaking skill. By using this strategy, the students will be able to express their ideas in speaking.Generally, it can be concluded that speaking is the most important skill that should be mastered well by all of English students because by speaking, the students are able to communicate each other. To make the students can speak well the teacher can use class meeting strategy in teaching speaking because by using this strategy, the students will be able to speak with the other enjoyable without fell nervous and afraid to make a mistake.